Clinical Outcome of Negative Rigid Esophagoscopy in Patients with Suspected Foreign Body Ingestion. (23rd August 2013) - Ong, Yew Kwang; Lim, Audrey; Lim, Chwee Ming
Abstract : Objectives: Identify the reasons and clinical outcome for negative rigid esophagoscopy (NRE) in patients with suspected foreign body (FB) ingestion. Methods: A retrospective chart review was performed on patients with a history of FB ingestion with negative rigid esophagoscopy over a 12‐year period. Patients with suspected FB ingestion underwent rigid esophagoscopy (RE) when they were symptomatic and/or when the radiological investigations revealed suspicious feature(s) of an FB. NRE patients were categorized as 1) passed out FB; 2) false positive indications for RE; or 3) migrated FB. Clinical outcomes were evaluated based on successful FB removal and complications following either FB ingestion or treatment related interventions. Results: 89 (12.3%) out of 723 patients who underwent rigid esophagoscopy for suspected FB ingestion had NRE. 61.8% (55/89) had spontaneous FB passage without any complications; 36.0% (32/89) had a false positive indication for RE; and 2.2% (2/89) had migrated FB necessitating neck exploration with successful removal of the offending FB. Abnormal calcifications seen on radiological investigation accounts for 34.4% of these patients having false positive indications for RE, with 2 patients having thoracic exploration to rule out a migrated thoracic esophageal FB. Conclusions: The prevalence of NRE in patients with suspected FB is low (12.3%). However, 36.0% of patients had rigid esophagoscopy performed due to false positive indication, and nearly a third of these patients were primarily due to abnormal calcifications seen on the radiological investigations.